2008
DOI: 10.1542/peds.2007-2704
|View full text |Cite
|
Sign up to set email alerts
|

Community-wide Intervention to Improve the Attention-Deficit/Hyperactivity Disorder Assessment and Treatment Practices of Community Physicians

Abstract: Quality-improvement interventions such as the one used in this study seem quite effective in improving primary care providers' practices at offices that express interest in improving the quality of care for attention-deficit/hyperactivity disorder. The design of the intervention, problems associated with improving and sustaining treatment monitoring, and issues related to generalizability of the intervention model are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
93
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 21 publications
4
93
1
Order By: Relevance
“…3,19 In previous investigations of this intervention model using practice-selected charts, we reported higher baseline levels of practice behaviors. 5,11 The present study's use of randomly selected patient charts, as opposed to physician self-reports or practice-selected patient charts, produced dramatically lower rates of evidence-based practice behaviors (ie, 14%-20% used teacher rating scales during assessments). The discrepancies between these different data collection modalities are considerable and should be considered in interpretation of the results of studies that use selfreports or reviews of nonrandomly selected charts.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…3,19 In previous investigations of this intervention model using practice-selected charts, we reported higher baseline levels of practice behaviors. 5,11 The present study's use of randomly selected patient charts, as opposed to physician self-reports or practice-selected patient charts, produced dramatically lower rates of evidence-based practice behaviors (ie, 14%-20% used teacher rating scales during assessments). The discrepancies between these different data collection modalities are considerable and should be considered in interpretation of the results of studies that use selfreports or reviews of nonrandomly selected charts.…”
Section: Discussionmentioning
confidence: 69%
“…The low rates of evidence-based ADHD treatment practices have repeatedly been found to be resistant to reliable implementation. 5,7 Additional intervention components (eg, community collaborations 20 or assignment of case managers [21][22][23] ) might possibly help parents and teachers to improve adherence to prescribed practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent models for enhancing mental health services in primary care [1][2][3][4] include outside psychiatric assessment and telephone consultation, 5 collaborative peer consultation, [6][7][8] mental health assessment skills training, 9 and collaborative care interventions. 10,11 As suggested in a recent review, these studies have revealed progress in improving provider care processes (eg, medication for attention-deficit/hyperactivity disorder [ADHD]; mental health assessment) and child symptoms (eg, ADHD, depression), but also call for larger and more rigorous trials.…”
mentioning
confidence: 99%